The Impact of Work-Family Conflict on Health Workers Burnout: The Mediating of Job Stress - Fitriani, Nita; Andriani, Chichi (Human Resource Management Studies, 2024)
The research investigates the impact of work-family conflict on health workers burnout, taking into account the mediating role of job stress. The research participants consisted of 70 health workers selected through total sampling techniques from all female health workers. Data analysis wa carried out using Structural Equation Modeling (SEM), with data processing using Partial Least Square (PLS). The results of the hypothesis test show that work-family conflict has a positive effect on burnout. Apart from that, job stress also influence burnout. From the test results it can also be proven that job stress is able to mediate the relationship between work-family conflict and burnout of health workers at the Pauh Kambar Community Health Center. These findings highlight the importance of reducing officer burnout to prevent a decrease in work effectiveness and efficiency that is less than optimal.